БИРИНШИ ҚАРАҚАЛПАҚ РОМАНЫ (ХХ әсирдиң 50 - жылларындағы түркий тиллес халықлары романлары типологиясы контекстинде үйренилиў мәселелери) - Бекбергенова, М.Д. (SCIENCE and SOCIETY, 2021)
This article examines the issues of studying the Karakalpak prose of the twentieth century, on the example of the analysis of the work of the Karakalpak writer A Begimov "Balıqshiniń qızı" ("The Fisherman's Daughter"). The issues of typology of the Karakalpak novel are studied, the problems of creative skill in the creation of artistic images in the first Karakalpak novels are analyzed. The images of Ayqız from the novel by A. Begimov "Balıqshınıń qızı", Botakoz from the novel by S. Mukanov "Botakoz", Kumush from the novel are considered in the historical and comparative aspect. A. Qadiri "Days bygone", etc. The problem of the typology of the novel is also being studied.
Keywords: novel; image; plot; typology; skill; epic; genre; tradition; theme; idea